Produk, Harga dan Promosi terhadap Keputusan Pembelian Rumah di BTP Residence Bekasi - Priscillia Ester Wijaya; Totok Sugiharto (IPM2KPE, 2024)
This research aims to analyze the impact of products, prices and promotions on house purchasing decisions at BTP Residence Bekasi. The location factor, as a key element in the property business, is a major consideration, but cannot be changed at this stage of the project. Therefore, this research focuses on evaluating factors that can be improved to influence purchasing decisions. The research method used is quantitative by collecting data through questionnaires filled out by 112 respondents, namely potential buyers who are in the affective stage of purchasing decisions, showing interest and taking actions such as location surveys and consultations via WhatsApp. The collected data was processed using the multiple linear regression method. The research results show that product, price and promotion have a positive and significant influence on the decision to purchase a house at BTP Residence Bekasi. Although location factors cannot be modified, an emphasis on them provides an idea of factors that can be improved to increase buyer attraction. In conclusion, this research contributes to understanding the determining factors of purchasing decisions in the property market, especially in East Bekasi Permai Residence Bekasi. The implications of these findings can help property developers to design more effective marketing strategies and increase their competitiveness in a competitive market. Keywords: Price, Purchase Decision, Product, Promotion